Factors Influencing Intermittent Preventive Treatment Optimal Uptake among Postnatal Women in La-Nkwantanang Madina Municipality - Kwarteng, Y.F. (University of Ghana, 2022)
Introduction: In Africa, where malaria is endemic, malaria-causing Low Birth Weight (LBW) kills between 62,000 and 363,000 newborns annually. In Ghana, nearly 5.9 million people were diagnosed with malaria in 2020, a considerable drop from the previous year (2019), which reported 6.7 million such cases. Ghana adopted a new IPTp-SP of MIP policy in 2004, which was updated in 2014, to reflect the updated policy of WHO 2012. In 2017, the uptake of IPTp3 was 43.0%, and IPTp5 was 8.9%, which was below the target of 85%. The study aimed at assessing factors influencing optimal intermittent preventive treatment uptake among postnatal women in the Pentecost hospital and Madina polyclinic in the LaNkwantanang Municipality of Ghana. Methods: This study was a facility-based, analytical cross-sectional study. The study population was made of postnatal mothers, of which a sample size of 366 was adopted. A simple random sampling was deployed in soliciting responses by administering a questionnaire. Data was gathered using an Open Data Kit (ODK) and analysed using STATA 15.1 for the chi-square test, Micro-Soft Excel for frequency distribution, and JAMOVI version 2.3.2 for regression analysis. Also, ethical approval was attained from Ghana Health Service ethical review board. Results: The study recruited 366 participants from Pentecost hospital and Madina Kekele Polyclinic in the LaNkwantanang Municipality in the Greater Accra region of Ghana. The optimal uptake of IPTp-SP was 29% (CI:0.385-1.95). Of the respondents, 261 took IPTp-SP 1 and 2, representing 79%, while those who received the optimum dose of IPTp-SP 3 plus was 29%. Also, about 50% of the midwives received training on IPTp-SP for the last two years. The respondent's income was statistically associated with IPTp-SP uptake (X2=15.7, p-value 0.03). In this study, the odds ratio for patients with optimal IPTp-SP uptake at the Madina Kekele Polyclinic compared to the Pentecost Hospital was 1.02 (95% CI: 0.677-1.56). The estimated difference in odds for patients optimal IPTp-SP uptake at the Madina Kekele Polyclinic compared to the reference group (Pentecost Hospital) was 0.08 (95% CI: 0.00-0.82). Age: The odds of optimal IPTp-SP uptake were higher for women aged 20-29 years (OR = 0.77, 95% CI = 0.346-1.73) and 30-39 years (OR = 0.86, 95% CI = 0.385-1.95) compared to women aged 10-19 years. However, the odds were significantly lower for women aged 40-49 years (OR = 1.18, 95% CI = 0.506-2.76) compared to women aged 10-19 years. Conclusion: This study found that optimal IPTp-SP uptake was below the national (85%) targets for IPTp3,4, and 5 among postnatal mothers.
MPhil. Applied Epidemiology and Disease Control
Keywords: Intermittent Preventive Treatment; Uptake; Postnatal; Antenatal